BS EN IEC 62841-2-12 AMDAA. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 2-12. Particular requirements for hand-held concrete vibrators (21st February 2022) - British Standards Institution,
No abstract available